In Search of a Brand for a Higher Education Institution through Its Architecture: The Case of the Polytechnic University of the Philippines - et. al., Jocelyn A, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The genesis of a formal education can be traced from the University of Bologna in Italy during the medieval period. The quest of making a mark in contributing to the development of the society through creation and transfer of knowledge has been the primordial concern. The race to be a top school has never been stiffer. A university cannot and should not be complacent with its status and must deliberately make efforts to improve their stature in the industry especially in teaching, research and extension. Over the years, architects have helped create a brand for top universities in Europe through its architecture. This trend was introduced in America and eventually in other parts of the world. In the Philippines, the establishment of the university found its way through its colonization by the Spaniards in the 16th century. The Spaniards brought with them the lessons of European architecture and educational systems. The paper chronicled the top universities in the Philippines and identified the image created through the architecture of their buildings with an end in view of providing a brand for the Polytechnic University of the Philippines. There is a very peculiar way by which the Polytechnic University of the Philippines evolved. The university is now situated in a compound intended for housing and its first building designed for a tenement housing. It is within this purview that this paper will provide the intervention which the administrators might consider in providing a brand for the university.